2018
DOI: 10.1080/01490419.2018.1530320
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Coastal Mean Dynamic Topography by Geodetic Combination of Tide Gauge and Satellite Altimetry

Abstract: The ocean mean dynamic topography (MDT) is the surface representation of the ocean circulation. The MDT may be determined by the ocean approach, which involves temporal averaging of numerical ocean circulation model information, or by the geodetic approach, wherein the MDT is derived using the ellipsoidal height of the mean sea surface (MSS), or mean sea level (MSL) minus the geoid as the geoid. The ellipsoidal height of the MSS might be estimated either by satellite or coastal tide gauges by connecting the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…On other coastlines, however, different dynamics apply. Tide gauge data, satellite altimetry, and ocean model simulations agree on the general features of the global coastal mean dynamic topography (Woodworth et al 2012;Andersen et al 2018), which shows smooth variations on eastern boundaries (except at the Strait of Gibraltar where the Mediterranean inflow allows for a step, Hughes et al 2015), but larger and sharper steps in places along western boundaries, with different models in particular showing significant differences in the latter case. The sharp steps appear to be associated with western boundary currents, the Gulf Stream in particular being a clear example (Higginson et al 2015), but the steps are smaller than those across the western boundary currents and occur equatorward of the main open-ocean step as if displaced in the direction of CTW propagation.…”
Section: The Low Frequency Limitsupporting
confidence: 52%
“…On other coastlines, however, different dynamics apply. Tide gauge data, satellite altimetry, and ocean model simulations agree on the general features of the global coastal mean dynamic topography (Woodworth et al 2012;Andersen et al 2018), which shows smooth variations on eastern boundaries (except at the Strait of Gibraltar where the Mediterranean inflow allows for a step, Hughes et al 2015), but larger and sharper steps in places along western boundaries, with different models in particular showing significant differences in the latter case. The sharp steps appear to be associated with western boundary currents, the Gulf Stream in particular being a clear example (Higginson et al 2015), but the steps are smaller than those across the western boundary currents and occur equatorward of the main open-ocean step as if displaced in the direction of CTW propagation.…”
Section: The Low Frequency Limitsupporting
confidence: 52%
“…Abulaitijiang et al 2015;Passaro et al 2016;Bonnefond et al 2018). As a result, the coastal geodetic MDTs derived from these data approximately agree at several centimetres level with the ocean models and tide gauge-derived MDT data (Ophaug et al 2015;Idžanović et al 2017;Andersen et al 2018). This shows that recent altimetry data may serve as an additional source for coastal gravity field and MDT modelling and validation.…”
Section: Introductionsupporting
confidence: 65%
“…Santamaría-Gómez et al (2011) showed that this combination (of a power-law and white noise model) represents the best approximation of the noise content for 275 GNSS station position time series. This combination was also implemented in studies concerned with VLM SAT-TG estimation (WM16; Kleinherenbrink et al, 2018;Ballu et al, 2019). In particular, the spectral index κ can contribute to detecting the intrusion of low-frequency signals in the differenced time series.…”
Section: Statistical Analysis: Trend and Uncertainty Estimationmentioning
confidence: 99%